The design and rationale of the cardiac REHABilitation to improve metabolic health in Hypertrophic CardioMyopathy (REHAB-HCM) Study - Matthew Cheung; Nathaniel Moulson; Jinelle C. Gelinas; Ali Daraei; Sarah M. Bradwell; Carolyn Taylor; Neil D. Eves; Graeme J. Koelwyn; Thomas M. Roston (American Heart Journal Plus)
Study objective: Hypertrophic cardiomyopathy (HCM) is the most common genetic myocardial disorder increasingly characterized by concomitant metabolic syndrome. Cardiac rehabilitation (CR) has been shown to improve metabolic parameters in populations with heart failure and myocardial infarction. However, there is a paucity of data on the impact of CR in the HCM population with metabolic syndrome. We designed the REHAB-HCM study to explore the feasibility, safety, and efficacy of CR in HCM patients with metabolic syndrome. Design: Prospective observation cohort study. Setting: A multi-disciplinary HCM clinic and Multidisciplinary Exercise-based Cardiac Rehabilitation program. Participants: Patients aged 18–80 years old diagnosed with HCM and metabolic syndrome, defined by the American Heart Association and American College of Cardiology guidelines, and the National Cholesterol Education Adult Treatment Panel III (NCEP-ATP III) criteria. Intervention: A structured 3-month CR program with 6 months extended follow-up of physical activity levels. Main outcome measures: Feasibility (e.g., attendance), safety (e.g., major adverse events and exercise-related harms), and efficacy pertaining to long term improvements in physical activity levels, metabolic health, cardiorespiratory fitness, quality of life, and systemic and cellular markers of inflammation. Conclusion: This prospective cohort study will address an important knowledge gap by evaluating the effect of an organized CR program in HCM patients and metabolic syndrome. It is anticipated that exercise and CR will be feasible and beneficial for this complex patient population without significant exercise-related harms.